AUDITOR'S ABILITY TO DETECT FRAUD: THE ROLE OF TRAINING AS A MODERATOR - Shita Tiara; Debbi Chyntia Ovami; Henny Zurika Lubis; Camelya Adelyani Br Hutagalung; Gadiez Salsabilla Panjaitan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The ability of auditors to detect fraud is a crucial aspect in maintaining the integrity and transparency of financial statements. In the midst of the complexity and dynamics of the business world, fraudulent practices in financial statements are growing, so auditors are required to have better skills and abilities in detecting these actions. The results showed that redflags had an effect on the auditor's ability to detect fraud, while the auditor's personality and time pressure had no effect on the auditor's ability to detect fraud. The training moderated the influence of auditor personality on auditors' ability to detect fraud, but did not moderate the influence of redflags and time pressure on auditors' ability to detect fraud.